PENERAPAN ASESMEN BERBASIS FLIPPED LEARNING PADA MATERI ZAT ADITIF DALAM MASA PANDEMI COVID-19 - Gati Eka Wening Uni; Wahyu Budi Sabtiawan; Wahono Widodo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This study aims to determine the implementation of flipped learning based assessments, to find out assessments in the learning process such as attitudes, knowledge and skills assessments and to identify obstacles in online flipped learning based assessments. This research uses a descriptive analysis method that is qualitative in nature with data analysis techniques in the form of observation of assessment based on flipped learning, tests, questionnaires. The results of this study are the implementation of the flipped learning based assessment that has been carried out to get very good results, seen at all meetings it has an average result of 3.8 which means that in the flipped learning based assessment the implementation is effective in learning. The results of the attitude assessment show that students have very good attitude criteria during the learning process. The assessment of knowledge shows that all students have a value above the KKM, which means that students understand the material taught online through flipped learning. While the skills assessment is carried out by means of a portfolio assessment which provides an overview related to the achievement of the results of students having an average value that meets the minimum completeness criteria. The obstacles in the implementation of this online flipped learning based assessment are the internet network that is not supportive and learning facilities that are incomplete so that students are slightly hampered when the learning process takes place.